PSCF and CWT methods as a tool to identify potential sources of 7Be and 210Pb aerosols in Granada, Spain. (October 2022) - Berriban, I.; Azahra, M.; Chham, E.; Ferro-García, M.A.; Milena-Pérez, A.; Nouayti, A.; Orza, J.A.G.; Brattich, E.; Tositti, L.; Piñero-García, F.; El Bardouni, T.; Ziani, H.; et al.
Abstract: This research is focused on studying the preferred source regions and the pathways of the air masses with high particulate concentrations impacting on the activity concentrations of 7 Be and 210 Pb aerosols in Granada atmosphere. For this purpose, three different source-receptor methods have been used: Cluster Analysis, Potential Source Contribution Function ( PSCF ), and Concentration Weighted Trajectory ( CWT ). Air filter samples were weekly collected and analysed in Granada university (Spain 37.177N, 3.598 W, 687m a.s.l.) during 12 years (2006–2017) for the activity concentration of 7 Be, and during 5 years (2010–2014) for the one of 210 Pb. The time series of the collected data indicate that the concentration of both radiotracers present a cyclical and seasonal pattern, in association with their origins and atmospheric conditions. Clustering analysis showed that the air masses arriving to Granada can be classified as: (1) tropical continental air masses coming from the Mediterranean Sea, (2) tropical and warm polar maritime air masses produced over the Atlantic Ocean, and (3) continental air masses originated over Europe and Northern Africa. The PSCF and CWT methods confirmed that the main source areas of 7 Be are located in the Atlantic coast of southern Morocco, and Northern Africa. On the other hand, southern France and the Algerian desert were found to be the main region sources of 210 Pb. In addition, the Mediterranean Basin has been postulated as a strong source region for 7 Be and 210 Pb. Furthermore, the PSCF and CWT models show that the regions with larger 7 Be/ 210 Pb ratios are located in the Atlantic Ocean, due to frequent stratospheric intrusions specially during the winter months. Highlights: A seasonal pattern of 7 Be and 210 Pb was identified in Granada, Spain. Back trajectory analysis was used to identify the origin and pathway of air masses. Potential sources regions of 7 Be and 210 Pb activity were investigated. Granada is affected by Mediterranean Sea, Atlantic Ocean, and Sahara. Mediterranean basin is the main source common of 210 Pb and 7 Be.